The Effect of Circuit Training Exercises and Set Systems on Learning Motivation Towards Discus Throw Results of Students of SMP Negeri 2 Pendalian IV Koto - Fery Ferdian; Umar; Sayuti Syahara; Didin Tohidin; Yovhandra Ockta (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The Problem of this research is that the schools observed have never excelled, especially in discus throwing competitions, both at the district, provincial and national levels. There are still many students whose throwing results are below the discus throwing.The lack of maximum student throwing results is due to the lack of student arm muscle power when throwing. This research is to see the effect of circuit training and training systems in terms of learning motivation on discus throwing results. This study uses an experimental method with a factorial design with a level of 2x2. The population of this study was male students of SMP Negeri 2 Pendalian IV Koto, totaling 74 people and number of samples from all treatment plans was 40 people, based on group division 27% high learning motivation level and 27% low learning motivation level. The learning motivation instrument is measured by angle. The data obtained were analyzed using two-way ANOVA and Tukey's test with a significance level of α = 0.05. The final results : (1) Overall there is a difference in the effect of circuit training and the discus throwing circuit training method. (2) There is an interaction between circuit training methods and system set training with learning motivation on the discus throwing results(3) There are differences in the results of discus throwing given the circuit training method and set system training at high learning motivation. (4) There are differences in the results of throwing discus given the circuit training method and set system training at low learning motivation.